GENOTIPE DAN SUBTIPE VIRUS HEPATITIS B PENDERITA YANG TERINFEKSI KRONIK AKTIF - Gondo Mastutik; Juniastuti Juniastuti; Ali Rohman; Mochamad Amin; Poernomo Boedi Setiawan (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2014)
Chronic activivity of Hepatitis B Virus (HBV) infection can lead to liver cirrhosis or hepatocellular carcinoma. The objective of thisstudy was to know by analyzing the distribution of HBV genotypes and subtypes from hepatitis B patients suffering from chronic activehepatitis B infection in Surabaya. The HBV genotypes were determined by comparing the S gene sequences to those kept in the GeneBank. The phylogenetic tree was constructed by means of the unweighted-pair group method using arithmetic averages. Furthermore,the subtypes were deduced based on the prediction of amino acid residues 116 to 183 of HBsAg on multiple sequences alignment withClustalW2. This study involved 20 sera obtained from patients suffering chronic active hepatitis B infection. After PCR and sequencing,it was found that 13 samples could be used for sequence analysis. The results showed that all sequences were clustered into HBV genotypeB. The subtype adw2 was identified from 12 of 13 sequences, whereas one (1) belonged to ayw1. The subtype adw2 is most prevalent inIndonesia, namely in the islands of Sumatra, Java, South Kalimantan, Bali, Lombok, Ternate, and Morotai, while ayw1 is found in theislands of Nusa Tenggara and Moluccas. Based on this study, it was found that the patients with HBV subtype adw2 were from Surabaya, whereas with ayw1 was from Nusa Tenggara. It can be concluded that the HBV infected patients with chronic active hepatitis B inSurabaya have the genotype B with subtype adw2 which was originally from Surabaya, whereas, ayw1 was a patient originally fromNusa Tenggara.